Origin, migration, and accumulation of carbon dioxide in the East Changde Gas Field, Songliao Basin, northeastern China - Yu-Ming Liu (KeAi Communications Co., Ltd., 2018)
Abstract CO2 reservoirs are widely distributed within the Yingcheng Formation in the Songliao Basin, but the extreme horizontal heterogeneity of CO2 content causes difficulties in the exploration and exploitation of methane. Former studies have fully covered the lithology, structure, and distribution of the reservoirs high in CO2 content, but few are reported about migration and accumulation of CO2. Using the East Changde Gas Field as an example, we studied the accumulation mechanisms of CO2 gas. Two original types of accumulation model are proposed in this study. The fault-controlled accumulation model refers to gas accumulation in the reservoir body that is cut by a basement fault (the West Xu Fault), allowing the hydrocarbon gas generated in the lower formation to migrate into the reservoir body through the fault, which results in a relatively lower CO2 content. The volcanic conduit-controlled accumulation model refers to a reservoir body that is not cut by the basement fault, which prevents the hydrocarbon gas from being mixed in and leads to higher CO2 contents. This conclusion provides useful theories for prediction of CO2 distribution in similar basins and reservoirs.